Inequality and the Environment: The Economics of a Two-Headed Hydra - Moritz A. Drupp; Ulrike Kornek; Jasper N. Meya; Lutz Sager (Center for Economic Studies and ifo Institute (CESifo), 2021)
Preserving environmental quality and addressing economic inequality both feature prominently in public discourse. Neither of these two issues can be fully understood in isolation, and policies aiming at one issue will increasingly have to consider interactions with the other. We synthesize theoretical mechanisms that underpin inequality-environment interlinkages, and take stock of the empirical evidence. Our review is structured into four main blocks, describing, first, how the distribution of environmental amenities and dis-amenities is associated with income and wealth, second, how economic inequality affects environmental outcomes, third, how the cost of environmental policy is often borne unequally, and, fourth, how both the distribution of environmental quality and economic inequality shape welfare considerations underlying public policy appraisal. We argue that it is crucial to consider inequality-environment interlinkages even if one's primarily concern is one or other of these issues, and close by highlighting a number of areas for future research.
Keywords: D31; D33; E25; Q52; Q56; 330; environment; inequality